MENINGKATKAN MOTIVASI BELAJAR MENGENAL WARNA PRIMER MELALUI BERMAIN PUZZLE LANTAI DI SLB MUHAMMADIYAH PAUH IX PADANG - Nur Novriani Sianturi; Yosfan Azwandi; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by the problems that researchers find Muhammadiyah schools SLB IX Padang Pauh mild mental retardation in children that the child is not motivated to learn about primary colors, children always seem lazy when invited to learn about color. Based on this research aims to prove that by playing puzzle floor can increase the motivation of learning about primary colors.The research was conducted over three weeks. This study used experimental approach in the form of Single Subject Research (SSR) with AB research design. The subjects were mild mental retardation children. The target is to see their behavior from the child's motivation to learn perseverance, tenacity, interest / concern in the study, not bored to learn the color and fun in learning colors.The results of this study indicate that, increasing the motivation to learn to know the primary colors mild mental retardation in young grade I / C in SLB Muhammadiyah Padang Pauh IX increased after receiving services through a puzzle floor. This is evident when the researchers conducted in two sessions ie baseline sessions before the intervention is given five times the observations, and the percentage of color recognize primary motivation lies in the range of 20%, 20%, 20%, 20% and 20%. Second session of the intervention (B) researchers explain how these measures play floor puzzle motivated children start learning about primary colors seen from the perseverance child, child tenacity, interest / attention to children, and children do not get bored to learn that in this condition lies in the range of 34%, 42%, 64%, 60%, 86%, 100%, 100%,. The results of this study are expected to benefit the teachers, and so further research can be an alternative to improve the child's motivation to learn about primary colors.